2023
DOI: 10.1007/s10096-023-04642-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of gastrointestinal infections: lessons learned from syndromic testing, Region Zealand, Denmark

Abstract: The aim of this study was to investigate the value of syndromic diagnostic testing for a better understanding of the epidemiology of gastrointestinal infections in Denmark. Here we evaluated the QIAstat-Dx® Gastrointestinal (GI) Panel 1 assay on 18,610 fecal samples requested for analysis for enteric pathogens in Region Zealand, Denmark, in 1 year (October 1, 2021, to September 30, 2022). In total, 6905 (37%) samples were detected positive for one or more diarrhoeal bacteria, viruses, and protozoa. The most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…One North American and one recent Danish publication present results from syndromic testing with multiplex PCR assays performed on large numbers of faecal samples and include coinfections in their results. They both report coinfections in more than 60% of EAEC-positive samples, which is similar to our study [ 49 , 52 ]. Neither study describes the characteristics of EAEC-positive samples.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One North American and one recent Danish publication present results from syndromic testing with multiplex PCR assays performed on large numbers of faecal samples and include coinfections in their results. They both report coinfections in more than 60% of EAEC-positive samples, which is similar to our study [ 49 , 52 ]. Neither study describes the characteristics of EAEC-positive samples.…”
Section: Discussionsupporting
confidence: 92%
“…EAEC was detected in 2% of 798 German children with diarrhoea compared to none in the healthy control group of 580 children [ 47 ], and in 4% of 719 faecal samples from 179 Danish day care children, out of whom 24% reported diarrhoea [ 48 ]. A recent Danish study found EAEC in 488 of 18,610 (2.6%) faecal samples when analysing all samples received at a microbiological laboratory over a period of one year with a multiplex PCR panel [ 49 ]. To our knowledge, this is the only study published so far that presents data from such syndromic panel testing of all samples from patients with diarrhoea received at a laboratory for a period of at least one year, and we believe there are no other published epidemiological studies on EAEC that include the adult population in any Nordic country.…”
Section: Introductionmentioning
confidence: 99%
“…The overall prevalence of rotavirus and adenovirus was 29.8% and 6.3% of tested samples, respectively, with 160 studies from 18 countries from 1980 to 2019, mainly the Middle East and North Africa region ( 17 ). RV and AdV dominated from February to April in Denmark, and 22% of the samples were positive for rotavirus in March ( 18 ). The prevalence of AdV was recorded (7%), followed by HRV (2%) in Saudi Arabia ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…With increased awareness of Cryptosporidium , technological advances, and adherence to the In Vitro Diagnostic Regulation (IVDR – EU 2017/746), there is potential for standardized and more accurate detection and surveillance of cryptosporidiosis in EU countries where cryptosporidiosis was previously overlooked [ 2 ].…”
Section: Introductionmentioning
confidence: 99%